The biological and functional restoration of spinal cord injury - JIAN Feng‐zeng; YANG Qi‐qi; DUAN Wan‐ru (Chinese Journal of Contemporary Neurology and Neurosurgery, 2024)
Spinal cord injury (SCI) is a severe central nervous system disease. Serious complications can occur as a result of loss of sensory and motor functions below the injury level and a consistent hostile response in the injury region. The quality of life is decreased and the prognosis is poor. Therefore, a functional restoration is essential for better outcomes. Restoration of the anatomical structure and microenvironment of the damaged region can be obtained by molecular drug modulation, neuroprotection, neuroregeneration, stem cell therapy, and biomaterial‐based tissue engineering. Functional restoration can be achieved by boosting neuroplasticity with activity‐based therapy or electrical stimulation, or by implanting interfaces that allowed accessibility to interactive devices. Combined therapy showed potentially better outcomes.